2012
DOI: 10.1093/jpids/pis077
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Rotavirus Gastroenteritis During a Community Outbreak in Chiapas, Mexico During the Postvaccination Era

Abstract: During this outbreak, dietary, socioeconomic, and environmental factors were independently associated with risk of developing rotavirus disease. Rotavirus vaccine also offered significant protection against rotavirus disease of any severity, emphasizing the value of vaccination as a simple and highly effective public health strategy for prevention of rotavirus illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
2
6
1
Order By: Relevance
“…This study has found that vaccinated children indwelling with three or more fellow children in the same house are significantly more likely to acquire Rotavirus infection compared to those indwelling with less than three fellow children. This finding is similar to the study done in Chiapas, Mexico in which children indwelling in a house with seven or more people were significantly more likely to acquire Rotavirus infection [19]. This is attributed by the fact that the mode of spread of Rotavirus infection is largely person-to-person transmission, hence as the number of children increases in the house likewise transmission rate increases.…”
Section: Discussionsupporting
confidence: 88%
“…This study has found that vaccinated children indwelling with three or more fellow children in the same house are significantly more likely to acquire Rotavirus infection compared to those indwelling with less than three fellow children. This finding is similar to the study done in Chiapas, Mexico in which children indwelling in a house with seven or more people were significantly more likely to acquire Rotavirus infection [19]. This is attributed by the fact that the mode of spread of Rotavirus infection is largely person-to-person transmission, hence as the number of children increases in the house likewise transmission rate increases.…”
Section: Discussionsupporting
confidence: 88%
“…Differences were noted in studies by Badani et al [19] from Yemen in 2014, Sanchez-Uribe et al [24], 2014 from Mexico who found G2P [4] and G9P [4]. This difference is due to the fact that both studies were able to do P genotyping unlike our study hence were able to report combination genotypes that existed in their respective region.…”
Section: Discussioncontrasting
confidence: 86%
“…In infants aged 0–6 months, the protective effect is stronger than in infants aged 7–12 months [ 20 ]. A study in Mexico by Sánchez-Uribe et al in children aged <36 months with rotavirus diarrhea showed that exclusively breastfed infants have a positive significant association with reduced risk of diarrhea caused by rotavirus ( p < 0.01) [ 21 ]. A study in the United States by Dennehy et al that aimed to determine the risk factors for the occurrence of rotavirus diarrhea in hospital among children aged <59 months showed a protective effect in infants aged <6 months who are exclusively breastfed in terms of the incidence of rotavirus diarrhea leading to hospitalization [ 22 ].…”
Section: Discussionmentioning
confidence: 99%